Comparative analysis of calculating sigma metrics by a trueness verification proficiency testing‐based approach and an internal quality control data inter‐laboratory comparison‐based approach. Issue 9 (6th August 2019) - Li, Runqing; Wang, Tengjiao; Gong, Lijun; Peng, Peng; Yang, Song; Zhao, Haibin; Xiong, Pan
Abstract: Introduction: Two methods were compared for evaluating the sigma metrics of clinical biochemistry tests using two different allowable total error (TEa) specifications. Materials and methods: The imprecision (CV%) and bias (bias%) of 19 clinical biochemistry analytes were calculated using a trueness verification proficiency testing (TPT)‐based approach and an internal quality control data inter‐laboratory comparison (IQC)‐based approach, respectively. Two sources of total allowable error (TEa), the Clinical Laboratory Improvement Amendments of 1988 (CLIA '88) and the People's Republic of China Health Industry Standard (WS/T 403‐2012), were used to calculate the sigma metrics (σCLIA, σWS/T ). Sigma metrics were calculated to provide a single value for assessing the quality of each test based on a single concentration level. Results: For both approaches, σCLIA > σWS/T in 18 out of 19 assays. For the TPT‐based approach, 16 assays showed σCLIA > 3, and 12 assays showed σWS/T > 3. For the IQC‐based approach, 19 and 16 assays showed σCLIA > 3 and σWS/T > 3, respectively. Conclusions: Both methods can be used as references for calculating sigma metrics and designing QC schedules in clinical laboratories. Sigma metrics should be evaluated comprehensively by different approaches.